PENANGANAN MASALAH GIZI BURUK DENGAN MENINGKATKAN PEMAHAMAN WARGA AKAN PENTINGNYA GIZI DI DESA PAGEDANGAN - Stacia Andani Fortunata; Maria Dewi Puspitasari Tirtanigntyas Gunawan Puteri; Laurensia Christli; Tabligh Permana; Filiana Santoso (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2019)
Children malnutrition is a crucial problem in developing countries including Indonesia. The root main cause of malnutrition is due to the lack of educational background and low economical condition, resulting in inadequate protein intake that still below the Recommended Dietary Allowance (RDA). It was recorded that 6.89% of children under five years old suffered from malnutrition in Desa Pagedangan, Tangerang Selatan. To overcome this problem, community service was conducted to increase nutritional awareness and fulfill the adequate amount of protein in daily basis. The community service covered seminars, cooking demo, and product development of healthy food. The seminar aimed to introduce the importance and benefit of healthy diet to parents, while cooking demo aimed to give ideas and encourage parents to prepare healthy diet. Some questionnaires were distributed after seminars and cooking demo to get the feedback from participant. The results showed both cooking demo and seminars were giving beneficial contribution for participant (83% were agree). The formulation of rice porridge with overripe tempe was conducted aimed to fulfill the RDI of protein with preferable sensory acceptance. The final product showed better sensory acceptance than commercial product with mean value 6.47±0.73 for overall acceptance by hedonic taste. The total protein content per serving able to fulfill 4.5/18 RDI of infants 7-11 months old.